N‐Type SnSe2 Oriented‐Nanoplate‐Based Pellets for High Thermoelectric Performance. Issue 8 (4th December 2017) - Luo, Yubo; Zheng, Yun; Luo, Zhongzhen; Hao, Shiqiang; Du, Chengfeng; Liang, Qinghua; Li, Zhong; Khor, Khiam Aik; Hippalgaonkar, Kedar; Xu, Jianwei; Yan, Qingyu; Wolverton, Chris; et al.
Abstract: It is reported that electron doped n‐type SnSe2 nanoplates show promising thermoelectric performance at medium temperatures. After simultaneous introduction of Se deficiency and Cl doping, the Fermi level of SnSe2 shifts toward the conduction band, resulting in two orders of magnitude increase in carrier concentration and a transition to degenerate transport behavior. In addition, all‐scale hierarchical phonon scattering centers, such as point defects, nanograin boundaries, stacking faults, and the layered nanostructures, cooperate to produce very low lattice thermal conductivity. As a result, an enhanced in‐plane thermoelectric figure of merit ZT max of 0.63 is achieved for a 1.5 at% Cl doped SnSe1.95 pellet at 673 K, which is much higher than the corresponding in‐plane ZT of pure SnSe2 (0.08). Abstract : A novel ecofriendly n‐type SnSe2 oriented‐nanoplate‐based thermoelectric material is demonstrated. A high power factor is achieved through defect chemistry and a low thermal conductivity is achieved by all‐scale hierarchical phonon scattering. Taken together, an enhanced in‐plane thermoelectric figure of merit ZT max of 0.63 is achieved for a 1.5 at% Cl doped SnSe1.95 pellet at 673 K.